Establishment of transgenic pigs overexpressing human PKD2-D511V mutant - Zhang, Yuan; Xu, Saifei; Jin, Qiao; Luo, Jianing; Gao, Ce; Jayaprakash, Sakthidasan; Wang, Huanan; Zhuang, Lenan; He, Jin (Frontiers in Genetics, 2022)
Numerous missense mutations have been reported in autosomal dominant polycystic kidney disease (ADPKD), which is one of the most common renal genetic disorders. The underlying mechanism for cystogenesis is still elusive, partly due to the lack of suitable animal models. Currently, we tried to establish a porcine transgenic model overexpressing human PKD2-D511V (hPKD2-D511V), which is a dominant-negative mutation in the vertebrate in vitro models. A total of six cloned pigs were finally obtained using somatic cell nuclear transfer. However, five with functional hPKD2-D511V died shortly after birth, leaving only one with the dysfunctional transgenic event to survive. Compared with the WT pigs, the demised transgenic pigs had elevated levels of hPKD2 expression at the mRNA and protein levels. Additionally, no renal malformation was observed, indicating that hPKD2-D511V did not alter normal kidney development. RNA-seq analysis also revealed that several ADPKD-related pathways were disturbed when overexpressing hPKD2-D511V. Therefore, our study implies that hPKD2-D511V may be lethal due to the dominant-negative effect. Hence, to dissect how PKD2-D511V drives renal cystogenesis, it is better to choose in vitro or invertebrate models.